Developing Learning Physics Multimedia Based on Local Wisdom of PALI District to Improve Student Learning Outcomes and Motivation - Tri Dani Kusuma; Linda Lia; Lukman Hakim; Yusuf Mian (STKIP Singkawang, 2023)
The purpose of this research is to develop a multimedia learning physics based on local wisdom in PALI Regency that is valid, practical, and has a potential effect on learning outcomes and students' learning motivation. The development research uses the Rowntree model which has three stages including the planning stage, the development stage, and the evaluation stage. The evaluation stage using Tessmer's formative evaluation includes self-evaluation, expert review, one to one evaluation, small groups and field tests. This research was conducted in class X MIPA 3 consisting of 25 students. The research instruments used are walkthroughs, questionnaires and tests. Expert validation results show that the developed multimedia is very valid with an average score of 3.70. The results of the practicality questionnaire show that the product developed is very practical by obtaining a one-to-one evaluation percentage of 81.3% and a small group percentage of 85.4%. Multimedia effectiveness in terms of N-gain with an average N-gain of 0.68 in the medium category. The results of the learning motivation questionnaire showed that's average value of 34 where students have moderate learning motivation. Thus, it can be concluded that multimedia learning physics based on local wisdom in PALI Regency can be valid and practical as well as effective in improving student learning outcomes, work and energy, and increasing student motivation.